Biologia, comportamento e morfologia de "Paraselenis" ("Spaetiechoma") "flava" (L.) ("Chrysomelidae": Cassidinae s. str.: Mesomphaliini) - Silva, Fernanda Fonsêca e, 1985- (2020)
Orientador: João Vasconcellos Neto